2022
DOI: 10.1002/adfm.202203787
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Discharge Induced Bulk‐to‐Nanoparticle Transformation: Nano High‐Entropy Carbide as Catalysts for Hydrogen Evolution Reaction

Abstract: High-entropy carbide (HEC) is a promising alternative to precious metal catalysts for the hydrogen evolution reaction (HER). However, the preparation of nanoscale HECs is a great challenge although many methods have been developed to prepare bulk HEC materials. Herein, an electrical discharge induced bulk-to-nanoparticle transformation method is reported, by which well dispersed sub-10 nm high entropy (MoWVNbTa)C nanoparticles with high-density surface defects can be directly obtained by centrifugation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…As an example, the sub-10 nm HETMC particles deliver high catalytic activity (a low overpotential of 160 mV at a current density of 10 mA cm À2 ) and long-term durability for the electrochemical hydrogen evolution reaction, confirming the potential application of HETMC particles in the field of energy conversion (see previous work reported in Ref. [28]).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…As an example, the sub-10 nm HETMC particles deliver high catalytic activity (a low overpotential of 160 mV at a current density of 10 mA cm À2 ) and long-term durability for the electrochemical hydrogen evolution reaction, confirming the potential application of HETMC particles in the field of energy conversion (see previous work reported in Ref. [28]).…”
Section: Resultssupporting
confidence: 73%
“…The sintering process parameters for this ceramic block were 1820 °C maintained for 60 min with a pressure of 30 MPa, and the rest of the sintering details were the same as those reported in our previous works. [9,28] The pulse discharge processing is illustrated in Figure 10. The HETMC ceramic block was employed as the positive (þ) electrode, i.e., the workpiece electrode, and a commercial molybdenum electrode wire with a 0.18 mm diameter purchased from Jinduicheng Molybdenum Mining Guangming Co., Ltd. was used as the negative (À) electrode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside the widely used cation regulation strategy, anion regulation has been tried to prepare new type high-entropy compounds, including phosphorus-boron, 99 Page 14 of 43 Chemical Science sulfide, 100 phosphorus-sulfide 101 . Recently, as illustrated in Fig.…”
Section: Anion Regulationmentioning
confidence: 99%
“…Besides the widely used cation regulation strategy, anion regulation has been tried to prepare new types of high-entropy compounds, including phosphorus–boron, 99 sulfide, 100 and phosphorus–sulfide. 101 Recently, as illustrated in Fig. 5h, Wang et al 99 reported a two-dimensional high-entropy metal phosphorus trichalcogenide Co 0.6 (VMnNiZn) 0.4 PS 3 , which possesses the strengths of tunable adsorption energy and a large specific surface area.…”
Section: Composition Regulationsmentioning
confidence: 99%